Relation of Epicardial Fat Thickness with Carotid Intima-Media Thickness in Patients with Type 2 Diabetes Mellitus. (9th May 2013) - Cetin, Mustafa; Cakici, Musa; Polat, Mustafa; Suner, Arif; Zencir, Cemil; Ardic, Idris
Abstract : Aims. The aim of this study was to investigate the relationship of echocardiographic epicardial fat thickness (EFT) with carotid intima-media thickness (CIMT), in patients with type 2 diabetes mellitus (T2DM). Methods and Results. A total of 139 patients with T2DM (mean age 54.3 ± 9.2 and 49.6% male) and 40 age and sex-matched control subjects were evaluated. Echocardiographic EFT and ultrasonographic CIMT were measured in all subjects. Patients with T2DM had significantly increased EFT and CIMT than those of the controls (6.0 ± 1.5 mm versus 4.42 ± 1.0 mm, P < 0.001 and 0.76 ± 0.17 mm versus 0.57 ± 0.14 mm, P < 0.001, resp.). EFT was correlated with CIMT, waist circumference, BMI, age, duration of T2DM, HbA1c in the type 2 diabetic patients. Linear regression analysis showed that CIMT (β = 3.52, t = 3.72, P < 0.001 ) and waist circumference (β = 0.36, t = 2.26, P = 0.03 ) were found to be independent predictors of EFT. A cutoff high risk EFT value of 6.3 mm showed a sensitivity and specificity of 72.5% and 71.7%, respectively, for the prediction of subclinical atherosclerosis. Conclusion. We found that echocardiographic EFT was significantly higher in patients with T2DM. Our study also showed that EFT was strongly correlated with waist circumference and CIMT as being independent of sex.